Personal believes - Barriers to vaccination against Covid_19 - A.H.I. Abu Shehab; A.V. Gurita; L. Luca; L.Ș. Burlea; A. Ciubara (European Psychiatry, 2022)
Introduction The ongoing global pandemic of Covid_19 had a huge pressure to accelerate the development process of Covid_19 vaccine. This acceleration of the vaccine appearance raised many concerns regarding the effectiveness and the adequate safety of the vaccine among general population.